2023
DOI: 10.4314/jasem.v27i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength and Resistance to Sodium Sulphate Attack of Concrete Incorporated with Fine Aggregate Recycled Ceramic Tiles

Abstract: In this experimental study, compressive strength and resistance to sodium sulphate attack of concrete incorporating recycled ceramic tiles (RCT) as fine aggregate were investigated. RCT was used as partial replacement for river sand at four levels (0%, 33%, 66%, 100%). Samples for sulphate resistance tests were immersed in 5% Na2SO4 solution for 180 days after they had been cured under water for 28 days, and were monitored for change in physical appearance, mass change and loss of compressive strength. From ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…From the study, it was found that the silica-lime reaction requires more water in addition to water required during hydration of cement as opined by Nwankwo and Job (2014), while the immediate workability decreases, the adsorbed water might be partially released during the hardening process (Soji, et al, 2021). This phenomenon may be attributed to the physical characteristics of the pozzolana i.e., particle size distribution, specific gravity and the of fineness of the particles of the pozzolans as reported by Ambrose, et al (2023); Cordeiro, et al (2012). The slump test was performed on the fresh concrete to determine its workability (BS EN 12350: 2019) (Usman, et al 2020)…”
Section: Workability Slump Resultsmentioning
confidence: 99%
“…From the study, it was found that the silica-lime reaction requires more water in addition to water required during hydration of cement as opined by Nwankwo and Job (2014), while the immediate workability decreases, the adsorbed water might be partially released during the hardening process (Soji, et al, 2021). This phenomenon may be attributed to the physical characteristics of the pozzolana i.e., particle size distribution, specific gravity and the of fineness of the particles of the pozzolans as reported by Ambrose, et al (2023); Cordeiro, et al (2012). The slump test was performed on the fresh concrete to determine its workability (BS EN 12350: 2019) (Usman, et al 2020)…”
Section: Workability Slump Resultsmentioning
confidence: 99%
“…The cubes (60) underwent a curing process in water at ambient temperature (28 days). The sample cubes were thereafter soaked in 10% Magnesium sulphate (MgSO4) solution, adopted from works by [44]- [46]. At 7, 14, 21, and 28 days, samples' compressive strength was evaluated.…”
Section: Resistance To Sulphate Attackmentioning
confidence: 99%